Carbon nanotube / silk fibroin composite film and preparation method thereof

Through the combination of wet stretching and hot pressing processes, silk fibroin is used to form a cross-linked entangled double network structure, which solves the problem of insufficient mechanical properties of carbon nanotube films, and achieves an efficient mechanical performance improvement and environmentally friendly preparation process.

CN119119526AInactive Publication Date: 2024-12-13SUZHOU UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411248298.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-06
Publication Date
2024-12-13
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Due to the poor mechanical strength and stability of traditional carbon nanotube composite films, and the use of toxic and harmful organic solvents during the preparation process, it is difficult to achieve the effective composite of the excellent performance of carbon nanotubes with polymers, and it does not meet the requirements of green and environmental protection, and it is mechanical. Performance needs to be improved.

Method used

Using a combination of wet stretching and hot pressing technology, protonated carbon nanotube bundles by chlorosulphonic acid or organic solvents, and introduced macromolecular segments of silk fibroprotein rich in hydrogen bonds to form mutual cross-linked and entangled double network structures to improve Mechanical properties of carbon nanotube films.

Benefits of technology

The mechanical properties of carbon nanotube films are significantly improved, including fracture strength and specific energy absorption value, and environmentally friendly preparation methods are adopted, which are suitable for large-scale industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119119526A_ABST
    Figure CN119119526A_ABST
Patent Text Reader

Abstract

The invention discloses a carbon nanotube / silk fibroin composite film and a preparation method thereof, and the preparation method comprises the following steps: dipping a carbon nanotube film in chlorosulfonic acid or an organic solvent, taking out the carbon nanotube film, applying a constant external force to the carbon nanotube film to stretch the carbon nanotube film, and carrying out hot pressing treatment to obtain a pretreated carbon nanotube film; and dipping the pretreated carbon nanotube film in the silk fibroin solution, taking out the carbon nanotube film, and carrying out hot pressing treatment to obtain the carbon nanotube / silk fibroin composite film. According to the invention, a method of combining a wet stretching process and a hot pressing process is adopted, and a protonation reaction between chlorosulfonic acid and carbon nanotubes is utilized, so that carbon nanotube bundles are reoriented and densified; and then the silk fibroin macromolecular chain segment rich in hydrogen bonds is introduced into the three-dimensional porous structure of the densified CNT film, so that the silk fibroin macromolecular chain segment and CNT form a cross-linked entangled double-network structure, more effective load transfer between CNT tube bundles is realized, and the mechanical property of the CNT film is effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of carbon nanotube composite films, and in particular to a carbon nanotube / silk fibroin composite film and a preparation method thereof. Background Art

[0002] Traditional carbon nanotube (CNT) films have poor mechanical strength and stability due to their loose internal structure and weak connections between tube bundles. In recent years, carbon nanotube composite films have attracted widespread interest and great attention due to their unique mechanical, electromagnetic, optical, chemical and thermal conductivity properties. Based on their unique physical and chemical properties, carbon nanotube composite films have good potential application prospects in nanoelectronic devices, flat panel displays, electrochemical detection, sensors, pollutant separation and even tissue engineering materials.

[0003] The preparation methods of carbon nanotube composite films usually include vacuum filtration, spin coating, liquid phase chemical deposition and solution blending. However, due to the high specific surface area of ​​carbon nanotubes themselves, strong interactions between carbon nanotubes, and poor compatibility between carbon nanotubes and polymers, carbon nanotubes are easily agglomerated in polymers and phase separated. Therefore, it is difficult to combine the excellent performance of carbon nanotubes with polymers in the above-mentioned traditional preparation methods. In addition, most of the above-mentioned methods require a large amount of toxic and harmful organic solvents to disperse carbon nanotubes and dissolve polymers. The preparation process does not meet the requirements of green environmental protection and is not conducive to large-scale industrial production. In addition, the mechanical properties of carbon nanotubes and their composite films also need to be improved, so it is urgent to develop a lightweight, soft, impact-resistant and stretchable carbon nanotube composite film. Summary of the invention

[0004] In order to solve the above technical problems, the purpose of the present invention is to provide a carbon nanotube / silk fibroin composite film and a preparation method thereof. The preparation method provided by the present invention has low cost and strong operability.

[0005] The present invention is achieved through the following technical solutions:

[0006] The present invention provides a method for preparing a carbon nanotube / silk fibroin composite film, comprising the following steps:

[0007] (1) immersing a carbon nanotube film in chlorosulfonic acid or an organic solvent, taking it out and applying a constant external force to the carbon nanotube film to stretch it, then removing excess chlorosulfonic acid or organic solvent, and performing a hot pressing treatment to obtain a pretreated carbon nanotube film; dissolving a lyophilized silk fibroin powder in a solvent to obtain a silk fibroin solution; the solvent is formic acid, lithium bromide aqueous solution, hexafluoroisopropanol, dimethyl sulfoxide, trifluoroacetic acid or a calcium chloride-ethanol-water ternary system solution;

[0008] (2) Immersing the pretreated carbon nanotube film obtained in step (1) in the silk fibroin solution, taking out the immersed carbon nanotube film and subjecting it to hot pressing treatment to obtain the carbon nanotube / silk fibroin composite film.

[0009] In order to improve the fracture strength of carbon nanotube films, replacing the weak van der Waals forces between carbon nanotubes with stronger interactions is an effective strategy. Hydrogen bonds are strong and widely present in nature, especially silk fibroin (SF) in natural silk fibers, with a strength of 4.2 to 167.4 kJ·mol -1 , much higher than the van der Waals force (0.4-4 kJ·mol -1 ). The secondary structure of SF mainly includes α-helical coil and β-sheet conformation. The β-sheet conformation gives silk fibers high mechanical strength because it contains a large number of hydrogen bonds from repeating peptide chains. During tensile strain loading, hydrogen bonds on the β-sheet conformation play a vital role in effectively dissipating molecular stick-slip deformation, giving natural silk fibers excellent mechanical properties. Based on this, infiltrating SF between carbon nanotube bundles can enable stronger SF-CNT and SF-SF interactions to replace the weaker van der Waals forces between CNT bundles in carbon nanotube films, thereby achieving more efficient load transfer between CNT bundles and effectively improving the mechanical properties of carbon nanotube films.

[0010] Furthermore, in step (1), the immersion time is 20 to 40 seconds.

[0011] Furthermore, in step (1), after taking out, a constant external force is applied to the carbon nanotube film within 20 to 40 seconds to stretch it to a deformation of 30 to 50%.

[0012] Furthermore, in step (1), the stretched carbon nanotube film is placed in an acetone solution to wash away the chlorosulfonic acid.

[0013] Furthermore, in step (1), the conditions for the hot pressing treatment are: hot pressing temperature is 140-160° C., pressure is 0.5-1.5 MPa, and time is 1-3 h.

[0014] Furthermore, in step (1), the organic solvent is selected from one or more of acetone, ethanol and benzene.

[0015] Furthermore, in step (1), the lyophilized silk fibroin powder is prepared by the following method: degumming raw silk with a degumming agent, dissolving the degummed silk fibroin fibers in a solvent, and then dialyzing, centrifuging, and lyophilizing to obtain the lyophilized silk fibroin powder.

[0016] Furthermore, the degumming agent is anhydrous sodium carbonate (Sodium carbonate), urea (Urea) or papain (Papain), preferably urea.

[0017] Furthermore, the solvent is formic acid, lithium bromide aqueous solution, hexafluoroisopropanol, dimethyl sulfoxide, trifluoroacetic acid or calcium chloride-ethanol-water ternary system solution, preferably lithium bromide aqueous solution.

[0018] In a specific embodiment, the method for preparing the lyophilized silk fibroin powder comprises the following steps:

[0019] S1. placing raw silk in a degumming agent solution, performing two heat treatments, washing and drying to obtain degummed silk fibers;

[0020] S2. dissolving the degummed silk fibers in a solvent to obtain a silk fibroin mixed solution;

[0021] S3. The silk fibroin mixed solution was dialyzed using a dialysis bag with a molecular weight cutoff of 8000 to 14000Da, and a silk fibroin suspension was obtained after centrifugation;

[0022] S4. freeze-drying the silk fibroin suspension to obtain the silk fibroin freeze-dried powder.

[0023] The silk fibroin suspension prepared in step S3 has uneven dispersion of silk fibroin, making it difficult to control the concentration, and the silk fibroin in liquid state is very easy to deteriorate.

[0024] Furthermore, the solvent for dissolving the lyophilized silk fibroin powder is preferably formic acid.

[0025] Freeze-dried solid silk fibroin is convenient for long-term storage and helps control the solution concentration during use, thus achieving better experimental repeatability. Redissolving it in formic acid can not only effectively remove impurities, but also promote the crystallization process of silk fibroin, further enhancing the structural density of the material, thereby improving its mechanical properties and stability.

[0026] Furthermore, in step (2), the concentration of silk fibroin in the silk fibroin solution is 1 to 7 wt %, preferably 3 to 7 wt %.

[0027] Furthermore, in step (2), the immersion time is 5 to 15 minutes, preferably 5 to 10 minutes.

[0028] Furthermore, in step (2), the conditions of the hot pressing treatment are: hot pressing temperature is 40-60° C., pressure is 3-5 MPa, and time is 20-40 min.

[0029] Furthermore, in step (2), after the hot pressing treatment, the step of placing the mixture at room temperature for 10 to 12 hours is also included.

[0030] The present invention also protects a carbon nanotube / silk fibroin composite film prepared by the method.

[0031] The carbon nanotube / silk fibroin composite film provided by the invention can be applied to the field of impact protection.

[0032] Beneficial effects of the present invention:

[0033] The present invention adopts a method combining wet stretching and hot pressing processes, and utilizes the protonation reaction of chlorosulfonic acid or organic solvents with carbon nanotubes to reorient and densify the carbon nanotube bundles; then, the hydrogen-bonded silk fibroin macromolecular chain segments are introduced into the three-dimensional porous structure of the densified CNT film, so that the silk fibroin macromolecular chain segments and CNTs form a mutually cross-linked entangled double network structure, thereby achieving more effective load transfer between CNT bundles and effectively improving the mechanical properties of the CNT film. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 Surface SEM images of carbon nanotube / silk fibroin composite films prepared with different degumming agents; (a) and (b) were degummed using anhydrous sodium carbonate, (c) and (d) were degummed using urea, and (e) and (f) were degummed using papain.

[0035] Figure 2 These are cross-sectional SEM images of carbon nanotube / silk fibroin composite films prepared using different degumming agents; (a) and (b) are degummed using anhydrous sodium carbonate, (c) and (d) are degummed using urea, and (e) and (f) are degummed using papain.

[0036] Figure 3 The tensile properties test results of carbon nanotube / silk fibroin composite films prepared with different degumming agents are shown in Figure 1. (a) shows the tensile properties of carbon nanotube / silk fibroin composite films prepared with different degumming agents at a strain rate of 2200s -1 (a) is a graph showing the dynamic tensile properties test results of carbon nanotube / silk fibroin composite films prepared with different degumming agents; (b) is a graph showing the quasi-static tensile properties test results of carbon nanotube / silk fibroin composite films prepared with different degumming agents.

[0037] Figure 4 The figures are tensile fracture morphologies of carbon nanotube / silk fibroin composite films prepared with different degumming agents; among them, (a), (b) and (c) are degummed with anhydrous sodium carbonate, (d), (e) and (f) are degummed with urea, and (g), (h) and (i) are degummed with papain.

[0038] Figure 5 At a strain rate of 2200s -1 The dynamic tensile properties test results of carbon nanotube / silk fibroin composite films prepared at different immersion times are shown below.

[0039] Figure 6 At a strain rate of 2200s -1 Dynamic tensile properties test results of carbon nanotube / silk fibroin composite films prepared with different concentrations of SF.

[0040] Figure 7 At a strain rate of 1600s -1 , 1900s -1 , 2200s -1 , 2500s -1 , 2800s -1 The following is a graph showing the dynamic tensile properties test results of the carbon nanotube / silk fibroin composite film prepared in Example 5.

[0041] Figure 8 At a strain rate of 1600s -1 , 1900s -1 , 2200s -1 , 2500s -1 , 2800s -1 The tensile fracture morphology of the carbon nanotube / silk fibroin composite film prepared in Example 5 below; (a), (b) and (c) are at a strain rate of 1600s -1 The tensile fracture morphology of (d), (e) and (f) are at a strain rate of 1900s -1 Tensile fracture morphology under strain rate of 2200s -1 Tensile fracture morphology under strain rate of 2500s -1 Tensile fracture morphology under strain rate of 2800s -1 Tensile fracture morphology. DETAILED DESCRIPTION

[0042] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.

[0043] The present invention provides a method for preparing a carbon nanotube / silk fibroin composite film, comprising the following steps:

[0044] (1) immersing a carbon nanotube film in chlorosulfonic acid or an organic solvent, taking it out and applying a constant external force to the carbon nanotube film to stretch it, then removing excess chlorosulfonic acid or organic solvent, and performing a hot pressing treatment to obtain a pretreated carbon nanotube film; dissolving a lyophilized silk fibroin powder in a solvent to obtain a silk fibroin solution;

[0045] (2) Immersing the pretreated carbon nanotube film obtained in step (1) in a silk fibroin solution, taking out the immersed carbon nanotube film and subjecting it to hot pressing to obtain a carbon nanotube / silk fibroin composite film.

[0046] Wherein, the silk fibroin freeze-dried powder is prepared by the following method:

[0047] S1. placing raw silk in a degumming agent solution, performing two heat treatments, washing and drying to obtain degummed silk fibers;

[0048] S2. dissolving the degummed silk fibers in a solvent to obtain a silk fibroin mixed solution;

[0049] S3. The silk fibroin mixed solution was dialyzed using a dialysis bag with a molecular weight cutoff of 8000 to 14000Da, and a silk fibroin suspension was obtained after centrifugation;

[0050] S4. freeze-drying the silk fibroin suspension to obtain the silk fibroin freeze-dried powder.

[0051] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.

[0052] Unless otherwise specified, the experimental methods used in the following examples are all conventional methods, and the materials, reagents, etc. used are all available from commercial sources unless otherwise specified.

[0053] In the following embodiments, a split Hopkinson pull rod is used to perform an impact tensile test to test the dynamic tensile properties of the film. The test method is as follows: the film is cut into a narrow strip sample with a length of 10 mm and a width of 1 mm, and the two ends of the sample are fixed on a paper mold with instant glue, and the test is performed after being placed in a constant temperature and humidity environment for 24 hours. A threaded chuck is used to clamp the sample between the piezoelectric force sensor and the incident rod, and the clamping distance is 5 mm. After setting the launch pressure, the high-pressure air chamber releases the air pressure to accelerate the bullet rod to hit the right end of the incident rod to form a compression wave. The compression wave is reflected at the free end face on the right side of the incident rod as a tensile wave and transmitted to the incident rod, and propagates to the interface between the incident rod and the sample. The wave signal on the incident rod is obtained by the resistance strain gauge, and the voltage signal at both ends of the incident rod and the piezoelectric sensor is collected by an oscilloscope.

[0054] In order to obtain the stress-strain curve from the voltage signal collected by the incident rod and the piezoelectric sensor, the strain rate and strain can be calculated using the incident wave signal and the transmitted voltage can be converted into stress to determine the stress-strain relationship. The average strain rate of the sample The strain ε(t) and the average stress σ(t) can be calculated according to the following formula:

[0055]

[0056] Where C0 is the speed of sound in the rod, which can be expressed as to calculate, (E is Young's modulus, ρ is the density of the rod). S is the initial length of the specimen, ε I is the incident wave recorded by the strain gauge attached to the center of the incident rod, F is the load converted from the incident voltage, and A S is the cross-sectional area of ​​the specimen.

[0057] Example 1

[0058] A method for preparing a carbon nanotube / silk fibroin composite film comprises the following steps:

[0059] (1) immersing the carbon nanotube film in chlorosulfonic acid for 30 seconds, taking it out and applying a constant external force to the carbon nanotube film within 30 seconds to stretch it to a deformation of 40%, then placing it in an acetone solution to wash away the chlorosulfonic acid, hot pressing it on a hot press at a temperature of 150° C. and a pressure of 1 MPa for 2 hours, and then leaving it at room temperature for 12 hours to obtain a pretreated carbon nanotube film; dissolving the lyophilized silk fibroin powder in formic acid to obtain a silk fibroin solution with a concentration of 1wt%;

[0060] (2) The pretreated carbon nanotube film obtained in step (1) is immersed in a 1 wt% silk fibroin solution for 5 min, the immersed carbon nanotube film is taken out, and hot-pressed on a hot press at a temperature of 50°C and a pressure of 4 MPa for 10 min, and then placed at room temperature for 12 h to obtain a carbon nanotube / silk fibroin composite film.

[0061] Wherein, in step (1), the lyophilized silk fibroin powder is prepared by the following method:

[0062] S1. 20 g of raw silk was placed in 600 mL of 8.0 mol / L urea solution, treated in a water bath at 90°C for 2 h, then treated again with the above urea solution under the same conditions for 1 h, washed thoroughly with warm water, and dried in an oven at 60°C to obtain degummed silk fibers;

[0063] S2. 10 g of degummed silk fiber was dissolved in 200 mL of 9.3 mol / L lithium bromide aqueous solution, and stirred at 60° C. for 60 min until the fiber was completely dissolved to obtain a silk fibroin / lithium bromide mixed solution;

[0064] S3. After the silk fibroin / lithium bromide mixed solution was cooled to room temperature, it was placed in a dialysis bag with a molecular weight cutoff of 14000Da, and then dialyzed in deionized water at 4°C for 72 hours, with the water changed every 8 hours. After centrifugation at a speed of 8000r / min for 10 minutes, a silk fibroin suspension was obtained;

[0065] S4. Place the silk fibroin suspension in a freeze dryer and freeze-dry for 48 hours to obtain the silk fibroin freeze-dried powder.

[0066] Example 2

[0067] A method for preparing a carbon nanotube / silk fibroin composite film is basically the same as that of Example 1, except that in step (1), urea is replaced by anhydrous sodium carbonate.

[0068] Example 3

[0069] A method for preparing a carbon nanotube / silk fibroin composite film is basically the same as that of Example 1, except that in step (1), urea is replaced by papain.

[0070] Example 4

[0071] A method for preparing a carbon nanotube / silk fibroin composite film is basically the same as that of Example 1, except that in step (2), the pretreated carbon nanotube film obtained in step (1) is immersed in a 3wt% silk fibroin solution for 10 minutes.

[0072] Example 5

[0073] A method for preparing a carbon nanotube / silk fibroin composite film is basically the same as that of Example 1, except that in step (2), the pretreated carbon nanotube film obtained in step (1) is immersed in a 5wt% silk fibroin solution for 10 minutes.

[0074] Example 6

[0075] A method for preparing a carbon nanotube / silk fibroin composite film is basically the same as that of Example 1, except that in step (2), the pretreated carbon nanotube film obtained in step (1) is immersed in a 7wt% silk fibroin solution for 10 minutes.

[0076] Example 7

[0077] A method for preparing a carbon nanotube / silk fibroin composite film is basically the same as that of Example 1, except that in step (2), the pretreated carbon nanotube film obtained in step (1) is immersed in a 5wt% silk fibroin solution for 5 minutes.

[0078] Example 8

[0079] A method for preparing a carbon nanotube / silk fibroin composite film is basically the same as that of Example 1, except that in step (2), the pretreated carbon nanotube film obtained in step (1) is immersed in a 5wt% silk fibroin solution for 15 minutes.

[0080] Example 9

[0081] A method for preparing a carbon nanotube / silk fibroin composite film is basically the same as that of Example 1, except that in step (2), the pretreated carbon nanotube film obtained in step (1) is immersed in a 5wt% silk fibroin solution for 20 minutes.

[0082] The surface SEM images of the carbon nanotube / silk fibroin composite films (Examples 1 to 3) prepared by different degumming agents were obtained by scanning electron microscopy (SEM). It can be seen from the figure that the surface of the carbon nanotube / silk fibroin composite film prepared by anhydrous sodium carbonate and papain as degumming agents is relatively rough, and more small CNT bundles are adhered together under the action of SF to form a relatively thick CNT bundle. The bundles are filled with SF but there are still a lot of gaps. The surface of the carbon nanotube / silk fibroin composite film prepared by urea as a degumming agent is relatively smooth, and SF is very uniformly and abundantly adhered to the surface of the CNT film, forming a relatively delicate and smooth surface.

[0083] To further analyze the internal morphology and structural changes of the carbon nanotube / silk fibroin composite film, the carbon nanotube film was cut using a focused ion beam and its cross section was observed using a scanning electron microscope. The characterization results of the composite film cross section are shown in Figure 2. Figure 2 As shown, from Figure 2 It can be seen that the thickness of the carbon nanotube / silk fibroin composite film prepared by urea degumming is the smallest, only 7.0μm. This is because there are many macromolecular segments in the β-folded conformation in the SF solution degummed by urea. During the drying process, the self-shrinkage of the SF molecules is strong and the densification effect is good. There are fewer gaps between the CNT bundles of the carbon nanotube / silk fibroin composite film prepared by urea degumming, indicating that the SF degummed by urea is distributed more evenly between the CNT bundles and has a better wrapping and adhesion effect on the CNT bundles. When subjected to external force, the combination of uniform shear deformation of the β-folded conformation and molecular stick-slip deformation makes the load transfer between adjacent CNTs more effective, greatly enhancing the mechanical properties of the CNT film.

[0084] The tensile properties of carbon nanotube / silk fibroin composite films prepared by different degumming agents were tested. The test results are as follows Figure 3 As shown. Figure 3 In (a), it can be seen that at a strain rate of 2200s -1 The dynamic mechanical properties of carbon nanotube / silk fibroin composite films prepared with different degumming agents were compared. The dynamic fracture strength and specific energy absorption values ​​of the carbon nanotube / silk fibroin composite films prepared with urea as the degumming agent were 1424.49MPa and 81.09MJ / m 3 , which is much larger than the composite film prepared by anhydrous sodium carbonate and papain as degumming agents (the dynamic breaking strength and specific energy absorption values ​​of the composite film prepared by anhydrous sodium carbonate as degumming agent are 826.16MPa and 68.39MJ / m 3 The dynamic breaking strength and specific energy absorption of the composite film prepared by papain as a degumming agent were 655.86MPa and 58.99MJ / m 3 ).from Figure 3 In (b), we can see the quasi-static tensile properties of the carbon nanotube / silk fibroin composite films prepared with different degumming agents. The quasi-static breaking strength, specific energy absorption value and modulus (867.86MPa, 71.81MJ / m 3 and 27.31GPa) are significantly greater than anhydrous sodium carbonate (646.58MPa, 57.28MJ / m 3 and 19.49GPa) and papain (568.24MPa, 58.59MJ / m 3 and 12.34GPa) as degumming agents. The content of β-folded conformation in the silk fibroin prepared by urea as a degumming agent is high, and it has a large self-shrinkage force. Under the action of silk fibroin, the gap between the CNT bundles in the dense CNT film is further reduced, and the interaction force between the bundles is enhanced; at the same time, the macromolecular chain segments of the β-folded conformation are long and have excellent mechanical properties. The CNT bundles are evenly filled with silk fibroin macromolecular chains, and the CNT bundles are well coated and adhered. The stronger interaction between SF-CNT and SF-SF replaces the weaker van der Waals force between the CNT bundles in the carbon nanotube film. When subjected to external force, the combination of uniform shear deformation of the β-folded conformation and molecular stick-slip deformation makes the load transfer between adjacent CNTs more effective, so that the CNT film exhibits better mechanical properties. In summary, the silk fibroin prepared by different degumming agents has different effects on improving the mechanical properties of CNT films. The mechanical properties of the carbon nanotube / silk fibroin composite film prepared by urea as a degumming agent are better.

[0085] At a strain rate of 2200 s -1 The tensile fracture morphology of carbon nanotube / silk fibroin composite films prepared under different degumming agents is shown in Figure 2. Figure 4 As shown in the figure, by comparison, it can be found that the composite film prepared by using anhydrous sodium carbonate and urea as degumming agents has an obvious fracture, and the CNT bundles extracted are relatively thick, and the surface is covered with a layer of SF, but the CNT bundles extracted by the composite film prepared by using urea as a degumming agent are longer and more evenly arranged. The number of CNT bundles extracted from the fracture of the composite film prepared by using papain as a degumming agent is small and slender, and the amount of SF attached to the surface is also small. In summary, through the corresponding testing and analysis of the carbon nanotube / silk fibroin composite film prepared by using anhydrous sodium carbonate, urea and papain as degumming agents, it is found that the silk fibroin solution prepared by using urea as a degumming agent has the best treatment effect on the carbon nanotube film and the greatest improvement in mechanical properties.

[0086] The test was performed at a strain rate of 2200 s -1 The dynamic tensile properties of the carbon nanotube / silk fibroin composite films (Examples 1 and 7 to 9) prepared at different immersion times are shown in the following test results. Figure 5 The test was performed at a strain rate of 2200s -1 The dynamic tensile properties of the carbon nanotube / silk fibroin composite films (Examples 1 and 4-6) prepared with different concentrations of SF are shown in the following table. Figure 6 The test results show that when the silk fibroin concentration is 5wt% and the immersion time is 10min, the carbon nanotube / silk fibroin composite film exhibits the best dynamic mechanical properties, and its fracture strength and specific energy absorption values ​​reach 1424.49MPa and 81.09MJ / m 3 , which were increased by about 192.9% and 163.5% respectively compared with the CNT film without SF treatment (the pretreated carbon nanotube film prepared in step (1) of Example 1).

[0087] The test was performed at a strain rate of 1600 s -1 , 1900s -1 , 2200s -1 , 2500s -1 , 2800s -1 The dynamic tensile properties of the carbon nanotube / silk fibroin composite film prepared in Example 5 are shown in the following test results. Figure 7 As shown in Figure 2, the fracture strength and specific energy absorption values ​​are at a strain rate of 1900s -1 It reaches its maximum value at about 1.8 GPa and 87.3 MJ / m 3Compared with the CNT film not treated with SF (the pretreated carbon nanotube film prepared in step (1) of Example 1), the breaking strength and specific energy absorption value increased by 241.6% and 175.9%.

[0088] At a strain rate of 1600 s -1 , 1900s -1 , 2200s -1 , 2500s -1 , 2800s -1 The tensile fracture morphology of the carbon nanotube / silk fibroin composite film prepared in Example 5 is shown in FIG. Figure 8 As shown, comparing (a), (d), (g), (j) and (m), at a strain rate of 1900s -1 The fracture of the lower composite film is relatively flat, and the length of the extracted tube bundle is relatively uniform. The others all show a serrated tear fracture, and the length of the extracted tube bundle is uneven, with a large length fluctuation. -1 The bundles extracted from the fracture of the lower composite film are denser and longer, and the surface of the bundles is evenly and fully covered with silk fibroin. -1 Under the strain rate condition, the interaction force between SF and CNT bundles and the uniform shear deformation and molecular stick-slip deformation of the long amino acid chains in SF are best exerted.

[0089] The above-described embodiments are only preferred embodiments for fully illustrating the present invention, and the protection scope of the present invention is not limited thereto. Equivalent substitutions or changes made by those skilled in the art based on the present invention are within the protection scope of the present invention. The protection scope of the present invention shall be subject to the claims.

Claims

1. A method for preparing a carbon nanotube / silk fibroin composite film, characterized in that: The following steps are involved: (1) immersing a carbon nanotube film in chlorosulfonic acid or an organic solvent, taking it out and applying a constant external force to the carbon nanotube film to stretch it, then removing excess chlorosulfonic acid or organic solvent, and performing a hot pressing treatment to obtain a pretreated carbon nanotube film; dissolving a lyophilized silk fibroin powder in a solvent to obtain a silk fibroin solution; the solvent is formic acid, lithium bromide aqueous solution, hexafluoroisopropanol, dimethyl sulfoxide, trifluoroacetic acid or a calcium chloride-ethanol-water ternary system solution; (2) Immersing the pretreated carbon nanotube film obtained in step (1) in the silk fibroin solution, taking out the immersed carbon nanotube film and subjecting it to hot pressing treatment to obtain the carbon nanotube / silk fibroin composite film.

2. The preparation method according to claim 1, characterized in that: In step (1), the immersion time is 20 to 40 seconds.

3. The preparation method according to claim 1, characterized in that: In step (1), after taking out, a constant external force is applied to the carbon nanotube film within 20 to 40 seconds to stretch it to a deformation of 30 to 50%.

4. The preparation method according to claim 1, characterized in that: In step (1), the conditions of the hot pressing treatment are: hot pressing temperature is 140-160° C., pressure is 0.5-1.5 MPa, and time is 1-3 h.

5. The preparation method according to claim 1, characterized in that: In step (1), the organic solvent is selected from one or more of acetone, ethanol and benzene.

6. The preparation method according to claim 1, characterized in that: In step (1), the lyophilized silk fibroin powder is prepared by the following method: degumming raw silk with a degumming agent, dissolving the degummed silk fibroin fibers in a solvent, and then dialyzing, centrifuging, and lyophilizing to obtain the lyophilized silk fibroin powder.

7. The preparation method according to claim 1, characterized in that: In step (2), the concentration of silk fibroin in the silk fibroin solution is 1 to 7 wt %.

8. The preparation method according to claim 1, characterized in that: In step (2), the immersion time is 5 to 15 minutes.

9. The preparation method according to claim 1, characterized in that: In step (2), the conditions of the hot pressing treatment are: hot pressing temperature is 40-60° C., pressure is 3-5 MPa, and time is 20-40 min.

10. A carbon nanotube / silk fibroin composite film prepared by the method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Flexible composite conducting film and preparation method thereof

    CN109401337A

  • Post-treatment method for greatly improving performance of carbon nanotube film and application

    CN116281963A

  • High-strength and high-toughness carbon nanotube composite film as well as preparation method and application thereof

    CN118063812A